Paleoenvironmental context of the evolution of the Baodun Culture at Chengdu Plain, Sichuan Province, China. (November 2019) - Huang, Ming; Zhu, Cheng; Ma, Chunmei; He, Kunyu; Xu, Jiajia
The Baodun Culture (4600–3700 a BP) is currently the earliest archeological culture found at the Chengdu Plain in southwestern China. Archeological evidence has shown that the Baodun Culture likely originated from the upper reaches of the Minjiang River, with two possible routes for human migration into the lower Chengdu Plain proposed: (1) At about 5000 a BP, favorable climatic conditions in the upper reaches of the Minjiang stimulated the growth of populations and the development of agriculture in the region. Due to this shift, some groups expanded from the upper Minjiang River to sites in the northern area of the Chengdu Plain, such as the Guiyuanqiao site; (2) during 4800–4300 a BP, a drying event occurred in the upper regions of the river valley causing a reduction in agricultural harvests and the migration of populations into sites – including the Baodun site – from this area of the Minjiang to the southwest piedmont of the Chengdu Plain. A multi-facetted study of the T3321 profile at Baodun site, including pollens, grain size, and geochemistry, demonstrates that after 6000 a BP, the climate of the Chengdu Plain shifted from cool, toward warmer and dryer conditions. However, as the Chengdu Plain is located in an alluvial fan, hydrothermal conditions here are still generally better than those in the upper reaches of Minjiang River. A change in the proportion of Concentricystes seen in the profile T3321 also indicates that after 4700 a BP, the lake and marsh areas associated with the Baodun site further decreased. However, as a result of this reduction, more terrestrial surfaces were exposed, providing favored space for Baodun Cultural groups in the area of the site. Due to such conditions, by about 4600 cal. a BP, people in the upper reaches of the Minjiang River had primarily moved to the southwest piedmont regions of the Chengdu Plain.